CD4+ T Cells Promote IgG Production in MHC-Independent and ICAM-1-Dependent Manners in Pristane-Induced Lupus Mice - Shuai Liu; Yu-mei Li; Jin-zhi Li; Shu-jun Wang; Ping Ji; Mei-yu Zhang; Ying Wang (Mediators of Inflammation)
Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by autoantibody production and chronic inflammation. The etiology and pathogenesis of SLE are complicated in which dysfunction of CD4+ T cells is largely engaged. In this study, we investigated the manners of CD4+ T cells in antibody production in a lupus-like mouse model through peritoneal injection of pristane reagent. With the increase in total IgG/IgM and autoantibody production after 6 months, CD4+ T cells exhibited activated phenotypes with the elevated CD44, ICOS, OX40, and PD-1 expression. Pristane injection induced the increase in IgM levels in both wild-type and T cell-deficient TCRα-/- mice whereas IgG, IgG1, and IgG2a production was impaired. When adoptively transferring CD4+ T cells into T cell-deficient mice or coculturing CD4+ T cells and B cells in vitro, it was found that CD4+ T cells derived from pristane-treated mice could help the production of total IgG as well as IgG1/IgG2a in a more efficient manner both in vivo and in vitro. While MHC was dispensable for IgG production, ICAM-1 likely functioned as an attenuating factor for IgG production. Our study thus reveals that CD4+ T cells in pristane-treated mice play important roles in IgG production, which implies the critical roles in the induction of pathological autoantibodies in MHC-independent and ICAM-1-dependent manners.